Death and bereavement across cultures - Parkes, Colin Murray; Laungani, Pittu; Young, Bill, 1959- (Routledge, 1997)
All societies have their own customs and beliefs surrounding death. This handbook explains how to offer appropriate and sensitive support to those from other cultures who are dying or bereaved.